1901 Tenn. Pub. Acts. 406, An Act to Incorporate the Town of Carthage, in Smith County, Tennessee, and Conferring and Defining the Corporate Powers Thereof, ch. 186, § 10. - (:unkn) unknown (My University, 1901)
Be it further enacted, That the Council shall have power by ordinance to . . . regulate the storage of gunpowder and other explosives, and noisome or offensive substances. . .
Keywords: GUNPOWDER - STORAGE